2011
DOI: 10.1097/tp.0b013e318204860b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretransplant Dialysis Modality and Duration on Long-Term Outcomes of Children Receiving Renal Transplants

Abstract: There is a linear increase in the risk of graft failure with the use of and increasing duration of pretransplant HD for living donor grafts. This indicates another reason to minimize the need for and duration of pretransplant HD in children with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…Twenty eight percent of pediatric recipients from 1995 to 2000 were preemptive and this group has the best 1-year allograft survival. Twenty eight percent of transplants followed HD, and 34% followed PD [33] . Butani et al [33] showed that longer duration of pre-transplant HD, but not PD, led to a linear increase in risk of allograft failure among living donor recipients.…”
Section: Transition To Esrd Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty eight percent of pediatric recipients from 1995 to 2000 were preemptive and this group has the best 1-year allograft survival. Twenty eight percent of transplants followed HD, and 34% followed PD [33] . Butani et al [33] showed that longer duration of pre-transplant HD, but not PD, led to a linear increase in risk of allograft failure among living donor recipients.…”
Section: Transition To Esrd Therapiesmentioning
confidence: 99%
“…Twenty eight percent of transplants followed HD, and 34% followed PD [33] . Butani et al [33] showed that longer duration of pre-transplant HD, but not PD, led to a linear increase in risk of allograft failure among living donor recipients. Transplantation conveys a 4-fold higher survival benefit compared to dialysis.…”
Section: Transition To Esrd Therapiesmentioning
confidence: 99%
“…The mean age of all patients when transplanted was 13.2 AE 5.2 yr (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and 48% were male. One recipient in the DD group received two DD transplants during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…In an (16). In addition, other studies that have examined variables associated with allograft survival have identified LD source to be associated with a survival advantage (8,18). While donor source is not the only predictor of long-term graft survival, it clearly plays a critical role with LDs providing the most durable option in pediatric recipients.…”
Section: Discussionmentioning
confidence: 96%
“…Children with end stage renal disease are especially vulnerable to the organ shortage, since their psychosocial and neurodevelopmental functioning is adversely affected by the uremic environment and any delay in transplanting them can have long term ramifications. Moreover, pre-emptive transplantation has been shown to improve long term graft survival in children [2] . These considerations have made it critical for health-care providers to minimize wait times on dialysis.…”
Section: Introductionmentioning
confidence: 99%